2013
DOI: 10.1186/1617-9625-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between cigarette smoking and suicide in psychiatric inpatients

Abstract: IntroductionCigarette smoking is the single largest preventable cause of death and disability in the industrialized world and it causes at least 85% of lung cancers, chronic bronchitis and emphysema. In addition smokers are at a higher risk from psychiatric co-morbid illness such as depression and completed suicide.MethodsWe conducted a cross-sectional survey in which we targeted all patients with serious mental illness (SMI) who were admitted in Razi mental health Hospital in Tehran, Iran. We recruited 984 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…There was no significant difference between smoking and gender in our study. In a study in Korea in middle and high school students, the most highly correlated variables with suicidal attempts were smoking, depression, and inhalation experience (48). There was a significant association between smoking and suicide attempt in our study, too.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…There was no significant difference between smoking and gender in our study. In a study in Korea in middle and high school students, the most highly correlated variables with suicidal attempts were smoking, depression, and inhalation experience (48). There was a significant association between smoking and suicide attempt in our study, too.…”
Section: Discussionsupporting
confidence: 63%
“…In another study on 950 psychiatric adult patients with serious mental illnesses who were admitted to Razi Mental Health Hospital in Tehran, Iran, 70% of samples (73.2% males and 26.8% females) were smokers, and 219 participants had a history of suicide attempt. In the regression analysis model, gender, age, and cigarette smoking were significantly related to previous suicide attempts (19).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study from Kosovo reported unclear findings, as daily smoking was associated with suicidal ideation among males but not females [ 60 ]. Eight studies [ 56 , 70 , 87 89 , 93 95 ] reported a positive association with non-fatal suicidal behaviour, while four studies [ 60 , 89 , 94 , 96 ] reported a null association.…”
Section: Resultsmentioning
confidence: 99%
“…Iran is a developing country where the smoking rate (14.8%) is lower than that observed in many developed countries. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%